Fatores de risco e mecanismos de proteção nas narrativas das famílias em situação de violência conjugal - Seidl, Marisol Lurdes de Andrade (Universidade do Vale do Rio do Sinos, 2008)
Taking as reference the notion of family resilience as interactive and dynamic process, in an ecological framework of human relations, this dissertation is geared to the identification of resilience in families with a history of couple violence. Couple violence has been largely investigated as a result of the traumatic and strong consequences for the victims and for being a relational process of difficult response by family members as well as by larger sectors of society. Throughout the narrative technique two cases were investigated of families with a history of violence. And through the ecological participation of the researcher in the Deputy Office it was studied the perceptions of the professionals. Family beliefs, organizational patterns and ways of communication were identified in relation to the violent events, the protection mechanisms and risk situations in families in different contexts. Among risk factors that generated vulnerability, beliefs about women´s roles as family support, passive and the p
Keywords: fatores de proteção e risco; resiliência familiar; violência conjugal; família; couples violence; family resilience; protection and risk factors; family; Ciências Humanas